Physiological demands of basketball refereeing during international competition - Leicht, A. S. (Journal of Science and Medicine in Sport, 2008)
To date, the physiological effects of elite competition on basketball players have been reported while very little information exists concerning the effects of elite competition on referees. Therefore, the aim of this study was to examine the physiological demands of basketball refereeing during international competition. Seven elite basketball referees volunteered for this study during a pre-Olympic women's basketball tournament. During each of the eight tournament matches, heart rate (HR), relative exercise intensity as a percentage of age-predicted maximum HR (HRmax), proportion of match time within the ACSM-defined exercise intensity categories were recorded for each referee during each quarter of and the entire match. Comparisons between quarters for each variable were conducted using one-way ANOVAs. There were no significant differences between quarters for any variable. Referees, using a two-referee per match format, worked at an average HR of 150 bpm (range 110-181 bpm) for each quarter of the match, equating to a relative intensity of >70% HRmax for the majority (not, vert, similar76%) of each quarter. Basketball refereeing during international competition results in significant physiological exertion at relatively high exercise intensities for Australian referees. Further studies will assist in the development of appropriate training programs for elite basketball referees to maintain and/or maximise performance.